2016
DOI: 10.1117/12.2233709
|View full text |Cite
|
Sign up to set email alerts
|

Thirty Meter Telescope (TMT) Narrow Field Infrared Adaptive Optics System (NFIRAOS) real-time controller preliminary architecture

Abstract: The Narrow Field Infrared Adaptive Optics System (NFIRAOS) is the first light Adaptive Optics (AO) system for the Thirty Meter Telescope (TMT). A critical component of NFIRAOS is the Real-Time Controller (RTC) subsystem which provides real-time wavefront correction by processing wavefront information to compute Deformable Mirror (DM) and Tip/Tilt Stage (TTS) commands. The National Research Council of CanadaHerzberg (NRC-H), in conjunction with TMT, has developed a preliminary design for the NFIRAOS RTC.The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…. send control commands to the wavefront correction devices, is rather short and of the order of 0.2-2 milliseconds (Gratadour et al, 2016;Kerley et al, 2016;Bouchez et al, 2014). This \low latency" requirement de¯nes the control bandwidth of the AO system as well as the stability and robustness of the closed-loop (Adkins, 2012).…”
Section: Ao Real-time Control Systemsmentioning
confidence: 99%
“…. send control commands to the wavefront correction devices, is rather short and of the order of 0.2-2 milliseconds (Gratadour et al, 2016;Kerley et al, 2016;Bouchez et al, 2014). This \low latency" requirement de¯nes the control bandwidth of the AO system as well as the stability and robustness of the closed-loop (Adkins, 2012).…”
Section: Ao Real-time Control Systemsmentioning
confidence: 99%
“…The system architecture is based upon commercial server hardware with a classical Matrix Vector Multiply (MVM) control algorithm. Intensive benchmarking have been conducted to support this architecture and have demonstrated that the performance requirements can be met by using a moderate number of existing off-the-shelf commercial boards, which in addition enable the use of a significantly simpler RTC algorithm (MVM) [14], [15] .…”
Section: Real Time Controllermentioning
confidence: 99%
“…The most recent hardware benchmarking results point to CPUs and Intel Xeon Phi coprocessors being preferred over GPUs. 13,14 The European Southern Telescope (ESO) has also moved on from a combination of FPGAs and Digital Signal Processors (DSPs) for its AO RTC 15 to a heterogenous architecture involving CPUs and GPUs for mathematical processing and FPGAs for the high-speed interfacing. 16,17 A similar scalable AO kernel involving an FPGA-based Network Interface Card (NIC) for peer-to-peer communication, with GPUs performing the intensive computational part, is explored in Perret et al 18 A more recent approach from ESO (called Green Flash) aims to compare competing technologies of co-processors, GPUs and FPGAs for use as the computing platform for the AO system on the E-ELT.…”
Section: Introductionmentioning
confidence: 99%